Schizostachyum longinternodium (Poaceae: Bambusoideae), a new species from Yunnan, China - Zheng, Chaohan; Lin, Rushun; Ni, Jingbo; Xia, Nianhe (Phytotaxa, 2014)
A new species, Schizostachyum longinternodium, is described and illustrated. It is closely related to S. funghomii, but differs by its shorter culm sheaths with protuberances on culm sheaths shoulders, prophyll with an acuminate apex and tubular connate filaments.